THE ROLE OF FINANCIAL MANAGEMENT DECISIONS IN OBTAINING FINANCING TO CONTRIBUTE TO RAISING THE STRENGTH OF THE COMPANY AND EXPANDING INVESTMENTS IN THE PUBLIC SECTOR OF THE STATE OF IRAQ - Hamza Kadhim Rishag (Scholar Express Journals, 2022)
The decisions of the financial management through which it seeks to support the capabilities of companies in opening investments in the industrial sector. The purpose of the study is to clarify the decision-making process and its impact on companies. One of the most important findings of the study is that we note that working capital is positive in the six years, and this indicates that the funds The permanent assets funded the fixed assets as a reality of the financial balance of the institution despite the decrease in the value of working capital compared to the rest of the years, and this means that the institution has a margin of safety to face any emergency. Managerial decision-making is at the heart of the work of executive leadership and the starting point for all activities and behaviors that take place within the facility, even the relationship and interaction with the external environment. The cessation of any kind of decision-making leads to the cessation of work and the cessation of activities and behaviour, the expansion of administrative organization in all aspects of its activities, and in greater contact with the public. The working capital needs in the past six years were positive, which indicates that stocks and accounts payable are more in value than bank advances and short-term debts. Working capital
Keywords: Role of financial management; financing; Raise the strength of the company; expanding investments